Analisis Kemampuan Membaca dan Menulis Al-Qur'an Siswa Kelas VII SMP Amanah 1 Helvetia - Aditia Saputra (Fakultas Agama Islam Universitas Tjut Nyak Dhien, 2023)
ABSTRAK This purpose aims to analyze the ability to read and write the Qur'an of seventh grade students of SMP AMANAH 1 who have just entered the school with a general elementary school background both public and private. It is said by the Prophet Muhammad (peace be upon him) in the hadiths of the Imam Bukhori that you are a person who understands and explain the Qur'an. We also know that Al-Qur'an is a source of islam as a key of a Muslim in carrying out his or her daily life and that it is necessary to learn and teach it in order to produce a Muslim man who is competent, cultured, and obedient to Allah as an islamic insan. The method used in this study is pendekatan kualitatif since the data is presented in kata-kata format. Dekskriptif penelitian is the type of penelitian that is used. According to the results of the study, Helvetia, a student in grade 7, High school Amanah 1, was able to read the Qur'an accurately and clearly in accordance with the teachings of tajwidi and Muslim scholars, as well as to translate it accurately and clearly after learning the as-syafi'i. Even though there are a few women who are similar but are struggling and haven't finished reading the Qur'an, there are still challenges to overcome when translating the Qur'an into Arabic with accuracy and clarity because they haven't yet studied principium imla'.